Member combination selection for product collaborative design under the open innovation model. (January 2023) - Chen, Chen; Zhang, Shusheng; Chu, Jianjie; Yu, Suihuai; Ding, Ning; Zhao, Hang; Su, Zhaojing; Fan, Hao
Highlights: Developing a synergy effect-based member combination selection (SE-MCS) method. This method considers the involvement of the customer in product collaborative design. Identifying the synergy effect indicators by analysing the characteristics of product collaborative design under the open innovation model. Quantifying the synergy effect indicators based on the interaction between members emphasized by collaboration. This proposed method's rationality and superiority is validated by illustrative example and results comparisons. Abstract: A temporary product collaborative design team (PCDT) formed by customers and candidate service providers is the main organization form required to complete the task of product collaborative design (PCD) under the open innovation model. Therefore, the aim of this study was to implement synergy effect-based member combination selection (SE-MCS) while ensuring customer participation in the PCD. First, the conceptual framework of SE-MCS method was developed to characterise the SE-MCS process that includes the customer. Second, SE-MCS indicators were determined by analysing the characteristics of PCD under the open innovation model, and the quantitative calculation methods for these indicators were provided. Subsequently, the mathematical model for SE-MCS considering customer participation was established, and a multi-objective optimisation algorithm was adopted to identify the optimal scheme. Finally, the formation of a design team for a beach waste collection vehicle was performed to verify the proposed method. The results showed that the proposed method is more suitable to implement SE-MCS of PCD under the open innovation model. It can facilitate the smooth operation of PCD tasks and improve the quality and efficiency of teamwork, thereby increasing customer satisfaction.